Agenesis of the corpus callosum, developmental delay, autism spectrum disorder, facial dysmorphism, and posterior polymorphous corneal dystrophy associated with ZEB1 gene deletion. Issue 9 (25th July 2017) - Chaudhry, Ayeshah; Chung, Brian H.; Stavropoulos, Dimitri J.; Araya, Marcela P.; Ali, Asim; Heon, Elise; Chitayat, David
Abstract : We report on a girl diagnosed prenatally with agenesis of the corpus callosum (ACC) on fetal ultrasound and MRI. On postnatal follow‐up she was noted to have developmental delay, facial dysmorphism, autism spectrum disorder, and posterior polymorphous corneal dystrophy (PPD). Array‐comparative genomic hybridization analysis (Array‐CGH) showed a 2.05 Mb de novo interstitial deletion at 10p11.23p11.22. The deleted region overlaps 1 OMIM Morbid Map gene, ZEB1 (the zinc finger E‐box binding homeobox transcription factor 1), previously associated with posterior polymorphous corneal dystrophy type 3 (PPCD3). To our best knowledge this is the first reported case with a deletion of the ZEB1 gene in an individual with ACC and PPD, showing that the haploinsufficiency of the ZEB1 is likely the cause of our patient's phenotype.